Armed Conflict And Schooling : Evidence From The 1994 Rwandan Genocide - Akresh, Richard (The World Bank, 2008)
To examine the impact of Rwanda's 1994 genocide on children's schooling, the authors combine two cross-sectional household surveys collected before and after the genocide. The identification strategy uses pre-war data to control for an age group's baseline schooling and exploits variation across provinces in the intensity of killings and which children's cohorts were school-aged when exposed to the war. The findings show a strong negative impact of the genocide on schooling, with exposed children completing one-half year less education representing an 18.3 percent decline. The effect is robust to including control variables, alternative sources for genocide intensity, and an instrumental variables strategy